Limits to parallel computation : P-completeness theory - Greenlaw, Raymond; Hoover, H. James; Ruzzo, Walter L. (Oxford University Press, 1995)
This book provides a comprehensive analysis of the most important topics in parallel computation.It is written so that it may be used as a self-study guide to the field, and researchers in parallel computing will find it a useful reference for many years to come.